2023
DOI: 10.3390/medicina59040749
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Chromatic Durability of White Spot Lesions through Employment of Infiltration Resin Treatment

Abstract: Background and Objectives: White spot lesions (WSLs) denote regions of subsurface demineralization on the enamel that manifest as opaque and milky-white regions. Treatment for WSLs is essential for both clinical and aesthetic reasons. Resin infiltration has been identified as the most efficacious solution for alleviating WSLs, but studies with long-term monitoring are scarce. The aim of this clinical study is to assess the color change stability of the lesion after four years of implementing the resin infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Almost all mothers who participated in our study at least supervised and 92.9% reported brushing the teeth of their children by themselves. In line with our finding, in previous studies [5,34,46,47,49,55,73,74], most of the parents were aware and adhered to supervised toothbrushing. However, the outcomes of some reports [19,28,30,35,38,44,57,64,75] were not in accordance with our findings and showed a lack of knowledge and practice regarding parental supervised toothbrushing among most of the participant parents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Almost all mothers who participated in our study at least supervised and 92.9% reported brushing the teeth of their children by themselves. In line with our finding, in previous studies [5,34,46,47,49,55,73,74], most of the parents were aware and adhered to supervised toothbrushing. However, the outcomes of some reports [19,28,30,35,38,44,57,64,75] were not in accordance with our findings and showed a lack of knowledge and practice regarding parental supervised toothbrushing among most of the participant parents.…”
Section: Discussionsupporting
confidence: 92%
“…White spot lesions, as in opaque and milky-white color, are the early signs of dental caries and, if not treated, restorative treatment is mandatory [55]. Nearly 12% of all children had white spot lesions and 16.67% had cavitated carious lesions in this study.…”
Section: Discussionmentioning
confidence: 51%
“…White spot lesions should be managed using a multifactorial approach. The most important strategy is to prevent demineralization and biofilm formation [42]. Certain approaches, such as professional fluoride applications, use of agents containing CPP-ACP and CPP-ACFP, microabrasion, macroabrasion, and resin infiltration, are preferred in the management of white spot lesions [39,42].…”
Section: Restorative and Aesthetic Approachesmentioning
confidence: 99%
“…The most important strategy is to prevent demineralization and biofilm formation [42]. Certain approaches, such as professional fluoride applications, use of agents containing CPP-ACP and CPP-ACFP, microabrasion, macroabrasion, and resin infiltration, are preferred in the management of white spot lesions [39,42]. It has been reported that the most effective approach among these treatment options is resin infiltration [39,42].…”
Section: Restorative and Aesthetic Approachesmentioning
confidence: 99%
See 1 more Smart Citation